FRI0385 Joint manifestations in patients diagnosed with idiopathic inflammatory myopathy: multicenter registry. (15th June 2017) - Hernández Flόrez, DC; Valor, L; Martinez, J; Joven, B; Nuno, L; Larena, C; Llorente, I; Barbadillo, C; Pena, P Garcia de la; Ruiz, L; Moruno, H; Cobo, T; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) comprise a heterogeneous group of autoimmune conditions. Joint involvement can be considered to be part of the IIM systemic manifestations, together with a possible gastrointestinal, cardiovascular and/ or pulmonary involvement. Although articular involvement in the IIM has been described as variable and non-specific with a chronic course it might be an early symptom of dermatomiositis in up to 30% of cases and in those patients with overlap syndromes. Objectives: To evaluate and to identify joint manifestations in IIM patients. Methods: We evaluated a cohort of 479 patients that included 12 hospitals in the Community of Madrid belonging to the IIM registry of the Society of Rheumatology of Madrid (SORCOM-REMICAM) with diagnosis from January 1980 to December 2014. All patients were diagnosed of IIM according to Bohan and Peter criteria (1). The presence of arthralgia and arthritis was considered. IIM were classified as dermatomyositis (primary and secondary dermatomiositis) (DM) and polymyositis (PM) including the rest of the patients (classification I). Also, IIM were classified (II) as primary polimiositis (PPM), primary dermatomyositis (PDM), overlap syndrome (OSd), juvenile myopathies (JM), cancer-associated myopathies (CAM), autoimmune necrotizing myopathy and inclusion body myositis (these were grouped as other myositis; OM). Results: We found 70 (18%) patients with acute arthritis (<6 weeks), 74 (19%) patients with chronic arthritis (>6 weeks) and 245 (65%) patients without any joint manifestations. Using the Tanimoto et al. criteria (1), the presence of erosive arthritis was observed in 149/479 (38.3%) of the patients. When comparing the joint manifestations in the PM and DM groups (n=250, 52.2% vs. n=229, 47.8%) no statistically significant differences were observed. However, assessing joint manifestations according to classification II, we observed that the highest prevalence was found in the OSd group, followed by the PDM group (p=0.0001). The group with less joint manifestations was JM compared to OSd and PDM (Table 1 . Conclusions: The presence of joint manifestations associated with IIM in our cohort is higher compared to other studies described in the literature so far and emphasize the importance of an accurate joint examination in these patients. The OSd group showed more joint manifestations which might be explained by the coexistence of SLE and MCTD patients in this group. Currently, no association between the clinical subtypes of IIM, overall, these results are encouraging and suggest that joint assessment in follow up may be helpful in differentiating subtypes of IIM. References: Bohan A, Peter JB. N Engl J Med 1975 Feb 13;292(7):344–7. Disclosure of Interest: None declared